Instrumentation Of Ex-Officio Rights Of Religious Courts Judge Related To Fulfilling Children And Wife's Rights Due To Divorce - Rohman, Adi Nur, Uni; Sugeng, Sugeng; Widyaningrum, Hesti (UI Scholars Hub, 2023)
Most of divorce cases in Indonesia have a negative impact on divorced children and wives. This is due to the lack of public legal knowledge especially wives who are entangled in divorce cases so that their rights are often ignored. Judges of the Religious Court, in this regard, have a very important role in the protection of the rights of children and wives through the instrumentation of ex-officio rights which, because of his position, he has special authority in deciding the divorce case. This research is a combination of normative and empirical juridical research by connecting the case approach and the legislative approach. The research was conducted at the Bekasi Religious Court using the interview, observation and literature study methods. This study aims to analyze the conception of the rights of ex- officio judges, the basis for their consideration and the mechanism of their instruments in issuing decisions on divorce cases and their relevance to Islamic law.